A Survival guide for new special educators - Billingsley, Bonnie S. (San Francisco, California : Jossey-Bass Inc., Publishers, 2013)
What every special education teacher needs to know to survive and thrive The Beginning Special Educator's Survival Guide provides relevant, practical information for new special education teachers across a broad range of topic areas. Drawing on the latest research on special educator effectiveness and retention, this comprehensive, go-to resource addresses the most pressing needs of novice instructors, resource teachers, and inclusion specialists. Offers research-backed, classroom-tested strategies for working with a variety of special needs students.
Getting the job done right -- Great beginnings -- Working with others -- Special education law -- Developing quality IEPs -- Organizing and managing your work -- Classroom and behavior management -- Collaboration and co-teaching -- Supporting your students -- Assessment and knowing your students -- Universal design for learning and technology -- Effective instructional practices and lesson planning -- Teaching reading -- Teaching writing -- Teaching mathematics -- Teaching content -- Teaching students with limited to pervasive intellectual disability.
Includes bibliographical references and index.
Keywords: SPECIAL EDUCATION